Penggunaan Kitab-kitab Rijal dalam Penilaian Periwayat Hadis - Azzami, Abdulloh; Arifin, Tajul (Asian Journal of Islamic Studies and Da'wah, 2024)
Rijal books play an essential role in hadith studies by providing detailed information on the biographies and evaluations of hadith narrators. Through this literature, hadith scholars can assess the reliability and credibility of narrators, which helps determine the authenticity of the hadiths they transmit. This article explores the methodology in rijal books, their relevance in contemporary hadith studies, and the challenges they face in the modern context. The methodologies used include sanad criticism, compiling the biographies of narrators, and evaluating reputations based on scholars' testimonies. Sanad criticism ensures the continuity and trustworthiness of the transmission chain, while narrator biographies provide a comprehensive view of the narrators' lives, education, and activities. Reputation evaluation gathers opinions from scholars who know the narrators. The use of rijal books remains relevant in hadith verification, sanad criticism, hadith education, and academic research. They also offer insights into the social, political, and cultural contexts of the narrators, which are crucial for interpreting hadiths in the modern context. However, there are several challenges in their use, including limited information, the influence of historical context, and the need to integrate modern methodologies. Digital technology offers broader access but also raises challenges of validity and reliability of information. Major rijal books such as Al-Tarikh al-Kabir by Imam al-Bukhari and Al-Jam'u Bayna Rijal al-Shahihayn by Ibn Qirani, as well as other works like Ushul al-Ghabah Fi Ma’rifatil Asma’is Shahabah and Al-Thabaqat al-Kubra, make significant contributions to hadith studies. By understanding the methodologies and challenges in using rijal books, we can better appreciate the complexity and importance of hadith studies in the Islamic tradition. These books remain an important reference for anyone wishing to delve into hadith science and ensure the authenticity and validity of hadith chains.